Sosialisasi Anti Bullying sebagai Strategi Preventif dalam Meningkatkan Kesadaran Sosial Siswa di SDN 13 Batu Bajanjang - Muhammad Alfian; Muhammad Ilman Azela; Megi Dwi Putra Nanda; Irsyadul Khairi; Hanna Zahra Insani Pristiwasa; Putri Sakinah; Refni Andini (CV. ITTC INDONESIA, 2026)
Bullying is a problem that still frequently occurs in elementary school settings and has the potential to hinder students’ social, emotional, and academic development. Students’ limited understanding of the forms and impacts of bullying was the primary reason for conducting this activity at SDN 13 Batu Bajanjang. The activity aims to enhance students’ knowledge and awareness of the dangers of bullying and the importance of fostering positive social interactions. The method employed was interactive outreach through presentation of materials, discussions, Q&A sessions, and evaluation supported by observation, interviews, and documentation. The results of the activity showed an increase in students’ understanding of bullying. Students also demonstrated a more caring attitude, respect for their peers, and the courage to report bullying incidents. These findings indicate that anti-bullying outreach is important to conduct on an ongoing basis to support the creation of a safe, comfortable, and child-friendly school environment.